2023
DOI: 10.1002/advs.202206648
|View full text |Cite
|
Sign up to set email alerts
|

Revealing Surfactant Effect of Trifluoromethylbenzene in Medium‐Concentrated PC Electrolyte for Advanced Lithium‐Ion Batteries

Abstract: Despite wide‐temperature tolerance and high‐voltage compatibility, employing propylene carbonate (PC) as electrolyte in lithium‐ion batteries (LIBs) is hampered by solvent co‐intercalation and graphite exfoliation due to incompetent solvent‐derived solid electrolyte interphase (SEI). Herein, trifluoromethylbenzene (PhCF3), featuring both specific adsorption and anion attraction, is utilized to regulate the interfacial behaviors and construct anion‐induced SEI at low Li salts’ concentration (<1 m). The adsorbed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 43 publications
1
30
0
Order By: Relevance
“…To circumvent the root shortcoming, its immediate sibling, propylene carbonate (PC), has been proposed as its convenient substitute due to a much lower melting point of −48.8°C. [51][52][53] Unfortunately, early research has revealed that the cointercalation of PC would inevitably occur and cause the exfoliation of graphite, leaving the failure of graphite in PC-based electrolyte. [54] With a deep understanding of the electrolyte, it is found that tuning the solvation sheath can mitigate this problem by introducing cosolvent.…”
Section: Improving the Bulk Ionic Conductivity With Low Melting Point...mentioning
confidence: 99%
“…To circumvent the root shortcoming, its immediate sibling, propylene carbonate (PC), has been proposed as its convenient substitute due to a much lower melting point of −48.8°C. [51][52][53] Unfortunately, early research has revealed that the cointercalation of PC would inevitably occur and cause the exfoliation of graphite, leaving the failure of graphite in PC-based electrolyte. [54] With a deep understanding of the electrolyte, it is found that tuning the solvation sheath can mitigate this problem by introducing cosolvent.…”
Section: Improving the Bulk Ionic Conductivity With Low Melting Point...mentioning
confidence: 99%
“…In addition, the conversion between sulfur and lithium sulfide unavoidably results in a massive volume change, further crumbling the cathode structure . To solve the abovementioned problems, a great variety of methods have been proposed, such as designing core–shell-structured cathode materials, functional binders, advanced electrolytes, and so on. Sulfurized polyacrylonitrile (SPAN) is a prospective sulfur cathode material because of its unique chemical structure and excellent electrochemical performance. , The low-order sulfur species (S 4 –S 2 ) are covalently bonded to the organic skeleton of pyrolyzed polyacrylonitrile chains, which helps mitigate the volume change during conversion. , More notably, it appears that no high-order polysulfides are observed in carbonate-based electrolytes, alleviating the shuttling effect . Unfortunately, the SPAN demonstrates sluggish reaction kinetics and poor cycling performance in ether-based electrolytes, which severely limits its application in practical Li–S batteries. , …”
Section: Introductionmentioning
confidence: 99%
“…[6] Amongst the various classes of additives used, [13] surfactants owing to their specific spatial organization [14] emerge as promising candidates to alleviate the interfacial interactions that stem from the SEI layer formation. [15] Herein, we oriented the scope of the role of surfactants as protectors/stabilizers of the SEI in the presence or absence of (mineral) salts comprising the SEI (i. e., LiF, LiOH, Li 2 CO 3 , Li 2 O). The following three surfactants have been selected, namely, lithium dodecyl sulfate (LiDS), polyoxyethylene ether Forafac 1110D (LiF1110), and lithium perfluoro octanesulfonate Forafac 1185D (LiFOS).…”
Section: Introductionmentioning
confidence: 99%
“…The ideal amount of the selected additive likely depends on its function in the cell and the amount needed to obtain the desired effect (especially at the interface of electrode/electrolyte) without having a significant negative influence on other properties impacting the performance [6] . Amongst the various classes of additives used, [13] surfactants owing to their specific spatial organization [14] emerge as promising candidates to alleviate the interfacial interactions that stem from the SEI layer formation [15] …”
Section: Introductionmentioning
confidence: 99%